Wall Street à Hollywood : une perspective de criminologie culturelle visuelle - Carla Nagels; Françoise Vanhamme (Criminocorpus)
As a mode of communication, the image gradually dwarfs the spoken and written word. Such a late modern mediascape (Appadurai) modifies our relationship to reality and shapes, or even manipulates collective representations, including those relating to deviance. This thesis, which is at the core of cultural visual criminology, frames our interest in film productions, where images of crime proliferate. In particular, this contribution focuses on the filmic presentation of financial deviance, an issue that hardly mobilizes policies despite the successive crises it generates. In that respect, we show how the content of eleven Hollywood blockbusters shapes a representation of financial transgression that suggests a socio-politically unmobilizing message, and which therefore participates in the perpetuation of the social order. To do so, the exploration of their script, staging and filmic techniques is related to the “naming-blaming-claiming” model (Felstiner et al.).